2021
DOI: 10.3389/fpubh.2020.617976
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Vulnerability and COVID-19 Incidence Among Louisiana Census Tracts

Abstract: Objective: To examine the association between the Centers for Disease Control and Prevention (CDC)'s Social Vulnerability Index (SVI) and COVID-19 incidence among Louisiana census tracts.Methods: An ecological study comparing the CDC SVI and census tract-level COVID-19 case counts was conducted. Choropleth maps were used to identify census tracts with high levels of both social vulnerability and COVID-19 incidence. Negative binomial regression with random intercepts was used to compare the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 13 publications
4
58
0
Order By: Relevance
“…The elucidation of nonlinear relationships between SVI and COVID-19 outcomes challenges existing literature on SVI and COVID-19 that has assumed or failed to question linearity in this relationship. 17,18 Other results, including the strong correspondence between Theme 3 (Minority Status & Language) and CFR hot spot status, confirm and extend existing conclusions in previous work. 14,17,19 Methodologically, we brought optimized hot spot analysis (OHSA) to bear on county-level case and death counts, and attempted to clarify broader regions of high COVID-19 impact as well as correct for reporting bias in counties with underreported cases and/or deaths.…”
Section: Discussionsupporting
confidence: 87%
“…The elucidation of nonlinear relationships between SVI and COVID-19 outcomes challenges existing literature on SVI and COVID-19 that has assumed or failed to question linearity in this relationship. 17,18 Other results, including the strong correspondence between Theme 3 (Minority Status & Language) and CFR hot spot status, confirm and extend existing conclusions in previous work. 14,17,19 Methodologically, we brought optimized hot spot analysis (OHSA) to bear on county-level case and death counts, and attempted to clarify broader regions of high COVID-19 impact as well as correct for reporting bias in counties with underreported cases and/or deaths.…”
Section: Discussionsupporting
confidence: 87%
“…Aligned with existing studies 27,29 , two PIDRs (e.g., male percentage and unemployment rate) were found to be significantly associated with a higher risk of COVID-19 infection in global models including SEM, SLM, and CAR model. The higher risk of getting infected with COVID-19 among the male population can be explained by several gender-related factors.…”
Section: Discussionmentioning
confidence: 54%
“…21,22 Although the spatially dynamic nature of infectious diseases (e.g., different spatial patterns of transmission) makes geospatial analysis a valuable tool to unveil the epidemiology, [23][24][25][26] there have been limited studies reporting the geospatial characteristics of PIDRs. 13,[27][28][29][30] Several studies have reported ethnic minorities, age, and other social vulnerabilities to be associated with a higher COVID-19 infection, yet spatial patterns were generally not included in the statistical models as independent variables. 27,29,30 Fortaleza and colleagues used multivariate regression and found that demographic density and distance from the state capital are robust predictors of COVID-19 prevalence in Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Biggs, et al. supports the utilization of the CDC SVI for identification of vulnerable groups in the context of COVID-19 retrospectively [6] . However, SVI's level of demographic granularity and temporal-spatial resolution is inadequate for supporting the decisions local governments have had to make during the pandemic.…”
mentioning
confidence: 94%